Good Culture Cooperation in Organizations in Global Perspective - Ujang Cepi Barlian (Postgraduate Program, State Institute on Islamic Studies Purwokerto, 2017)
Culture in a broad sense is a dinamic value system in a variaties of life that go on for a long enough periode of time as the result and or the attitude of human’s guidance. Culture is belonges to the people. The difference culture of a society fr om the other lays on the it’s development in fulfilling all of the society’s need. Naturally culture is very hard to understand ,invisible, implicitly, and usually to be considered as a usual thing. But all of the organizations develope a set of understanding and an implicited order that regulates the everydays atitude in the work’s place. Organization culture is a part of the existing culture. This culture is very important for the development of an organization both in the state and private fields as well. In the state field, often happened that the state program which has adificulty, and it is usually culter considerated to be responsible to. The values that become the loading program has not yet socialized or culture is considered to be very difficult to change. If there is a new value that its implementation needs and the changes considered to be a subjection base by the state to that new culture is culture